System ewaluacji unijnego wsparcia wobec wsi i rolnictwa a społeczna odpowiedzialność oraz zasady good governance - Wieliczko, Barbara (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
Good governance principles are considered by the European Union to be a basic indicator serving in the assessment of the quality of the Community’s public management. Therefore, these principles should be treated as a reference point in the process of building all the necessary elements of the system of implementation of the EU tasks and activities. The same applies to the Common Agricultural Policy and to supporting within it the development of agriculture and rural areas. Following this the evaluation system should respect the good governance principles in most complex way that is possible and achievable. However, up to now, the development of the EU evaluation culture has not reached the level of comprehensive actual fulfillment of these principles and for the evaluation process to lead to improving the effectiveness and efficiency of the CAP. Moreover, if the EU involvement in supporting the development of social responsibility of the agriculture is worth underlining it should be conducted via the introduction of different rules and regulations applicable in this sector, which combined with the competition typical of this part of the economy should lead to development of socially responsible agriculture.